1970
DOI: 10.5636/jgg.22.393
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Type of Electron Temperature Probe

Abstract: It has already been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Since the memory of the recorder on board the satellite was limited, only 4 to 6 orbits of data per day were transmitted to the data acquisition station at the Kagoshima Space Center. The electron density and electron temperature were measured by an impedance probe in an upper resonance mode (Watanabe and Oya, 1986) and a resonance recti®cation probe (Hirao and Oyama, 1970), respectively. The relative error of the electron density measurements is about 10% and the maximum error of the electron temperature is about 50 K. It should be pointed out that normally the F2 layer peak of the ionosphere is lower than the altitude of the satellite (600 km), although the peak might occasionally move to above 600 km around equator during the postsunset period (Su et al, 1997).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Since the memory of the recorder on board the satellite was limited, only 4 to 6 orbits of data per day were transmitted to the data acquisition station at the Kagoshima Space Center. The electron density and electron temperature were measured by an impedance probe in an upper resonance mode (Watanabe and Oya, 1986) and a resonance recti®cation probe (Hirao and Oyama, 1970), respectively. The relative error of the electron density measurements is about 10% and the maximum error of the electron temperature is about 50 K. It should be pointed out that normally the F2 layer peak of the ionosphere is lower than the altitude of the satellite (600 km), although the peak might occasionally move to above 600 km around equator during the postsunset period (Su et al, 1997).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The electron temperature and density data used in the study were obtained from the observations made during 1981-82 by an electron temperature probe (Hirao and Oyama, 1970) and an impedance probe (Oya et al, 1986) on board the Hinotori satellite which was in a circular orbit at an altitude of -600 km. The inclination of the satellite was 31 degrees.…”
Section: Observationsmentioning
confidence: 99%
“…Almost without exception the surface of the electrode is contaminated. However even we remove the effect of electrode contamination or use the instrument which can avoid the electrode contamination (Hirao and Oyama, 1970;Oyama and Hirao, 1976), T e measured by DC Langmuir probe is higher than model T n (Oyama et al, 1980;Duhau and Azpiazu, 1985;Amemiya et al, 1985), although very rarely we observed T e which is very close to T n (Hirao and Oyama, 1973;Rohde et al, 1993).…”
Section: Introductionmentioning
confidence: 92%